A zebrafish and mouse model for selective pruritus via direct activation of TRPA1 - Esancy, Kali (eLife, 2018)
Little is known about the capacity of lower vertebrates to experience itch. A screen of itch-inducing compounds (pruritogens) in zebrafish larvae yielded a single pruritogen, the TLR7 agonist imiquimod, that elicited a somatosensory neuron response. Imiquimod induced itch-like behaviors in zebrafish distinct from those induced by the noxious TRPA1 agonist, allyl isothiocyanate. In the zebrafish, imiquimod-evoked somatosensory neuronal responses and behaviors were entirely dependent upon TRPA1, while in the mouse TRPA1 was required for the direct activation of somatosensory neurons and partially responsible for behaviors elicited by this pruritogen. Imiquimod was found to be a direct but weak TRPA1 agonist that activated a subset of TRPA1 expressing neurons. Imiquimod-responsive TRPA1 expressing neurons were significantly more sensitive to noxious stimuli than other TRPA1 expressing neurons. Together, these results suggest a model for selective itch via activation of a specialized subpopulation of somatosensory neurons with a heightened sensitivity to noxious stimuli.